ANALISIS PENGARUH JUMLAH NELAYAN, KAPAL ALAT TANGKAP IKAN DAN AKI TERHADAP PRODUKSI PERIKANAN SEKTOR PERIKANAN TANGKAP DI JAWA TENGAH - Irna Faridatul Khasanah; R. A. Norromadani Yuniati; Farizi Rachman (Proceeding Maritime Business Management Conference, 2024)
Central Java Province is one of the provinces that contribute to increasing the volume of fishery production in Indonesia. The purpose of this research is to analyze the factors influence the ammount of production of marine capture fisheries subsector in Central Java Province. The sample used in this research was a saturated sample totaling 140 samples. Hypothesis testing is conducted using multiple linear regression analysis methods. The result the research on the marine capture fisheries subsector showed that partially the number of fishermen, boats and fishing gear did not affect the ammount of production. Furthermore, the number of fish consumption has a significant positive effect on total production. The lack of influence of the number of fishermen, boats and fishing gear can be influenced by the existence of government policies, the number of fish populatoins, the fishing season and technology used.